التعاون الاقتصادي العربي في مجال النفط - هرمز نور الدين; الخليل فادي; العيسى دريد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعد صناعة النفط من أهم النشاطات التي يمكن أن تسهم في زيادة التعاون بين الدول العربية، ولاسيما وأنها تشتمل على سلسلة طويلة من المراحل تتيح فرصاً للتعاون سواء على الصعيد الثنائي أو الإقليمي أو الدولي. ويتمثل ذلك في مجالات الاستكشاف، والإنتاج، والتكرير، والتصنيع، والنقل، والتوزيع، والتسويق. تهدف الدراسة إلى استعراض دور النفط في تعزيز التعاون في مجال الطاقة بين الدول العربية من خلال استعراض المشاريع العربية المشتركة القائمة حالياً في الدول العربية في مجال النفط. كما تستعرض الدراسة واقع الشركات المشتركة المنبثقة عن منظمة الأقطار العربية المصدرة للبترول (أوابك) ودورها في تعزيز التعاون بين الدول العربية في هذا المجال, وآفاق التعاون العربي في مجال الطاقة. The oil industry is considered one of the main activities that contribute to increasing the cooperation among the Arab countries. It includes a long chain of stages that offers cooperation opportunities on the dual, regional, or international levels. This is represented in the areas of discovery, production, refinery, industry, transportation distribution and marketing. This study tries to illustrate the role of oil in enhancing the cooperation in the field of energy among the Arab nations through demonstrating the existing mutual Arabic projects in the Arab nations in the field of oil. It also demonstrates the status of the mutual companies that OAPEC and their role in enhancing the cooperation among the Arab nations in this field and the horizon of the Arab cooperation in the field of energy.